Redox metabolism in cell senescence: focusing on contributions from the metabolomic field - Chacón, Eliana; Grünwaldt, Guillermo; Marmisolle, Inés; Martínez, Jennyfer; Quijano, Celia (Frontiers in Molecular Biosciences, 2026)
Cell senescence is triggered by stressful stimuli, including telomere attrition, genotoxic agents, and strong mitogenic signals. This state is characterized by proliferation arrest and acquisition of a senescence-associated secretory phenotype. Senescent cells secrete growth factors, chemokines, cytokines, proteases, and other factors that can impact the cell’s microenvironment, promoting aging and the development of age-associated diseases. These discoveries have emphasized the need for a detailed analysis of the senescent phenotype. Redox alterations are one of the hallmarks of cellular senescence, and are required to maintain the senescent phenotype. Here, we review current information on senescent cell’s redox metabolism, with a special focus on metabolomic profiling of human fibroblasts. We describe metabolic pathways involved in redox homeostasis, in particular glutathione metabolism, that undergo reprogramming in cell senescence, and links with the senescent phenotype.